A transformação do homeschooling, da contracultura à extrema-direita - Camargo, Edivan Cesar Gomes de (2024)
Domestic Education, currently known as homeschooling, is a type of teaching in which those responsible for children teach them at home, deciding how, when and what to teach, exercising total control over the education of their daughters and sons. This form of teaching was also adopted in the context of counterculture, a transgressive movement from the 1960s and 1970s that criticized various aspects of bourgeois society (promotion of wars, inequality between sexes, moral institutions such as marriage and, above all, the authoritarian and ideological reproduction of school institutions). Based on this critical spirit, communities were founded, generally rural, that proposed to be economically and institutionally self-sufficient. Within these communities, an education model that became known as homeschooling was adopted, through which a world view that would be more fair and egalitarian was transmitted to children. In the first decades of the 21st century, supporters of the Brazilian far-right political spectrum have been raising this flag. These right-wing extremists believe that the school is doctrinaire, teaching “leftism” and “gender ideology”, which, according to them, attacks supposed moral values of the family, in reality values of the so-called culture Western, Judeo-Christian origin. Furthermore, they consider it a waste of money, especially in the case of private schools. These people argue that those responsible for children can provide an education by teaching only their moral and political values. In this dissertation, the transformations that the extreme right made in homeschooling were explored so that it met its objectives. To assist in this task, books and academic works that addressed the subject were used. With these tools, the “said” and, mainly, the “unsaid” were investigated in the selected works that were displayed on the website of the National Association of Home Education (ANED), in order to understand how such publications served as intellectual support for the interested in homeschooling from the far-right perspective.